Spatial pattern completion deficits in older adults - Paleja, Meera; Spaniol, Julia (Frontiers in Aging Neuroscience, 2013)
Aging may have an impact on the CA3 autoassociative network of the hippocampus, posited by computational models as supporting pattern completion. Twenty-five young (YAs) and 25 older adults (OAs) performed a spatial pattern completion task using a computerized navigational paradigm analogous to a rodent pattern completion task reliant on the CA3. Participants identified a previously seen goal location, and the availability of distal cues in the environment was manipulated such that 0, 2, or 4 cues were missing. Performance in both groups declined as a function of decreased cue availability. However, controlling for age differences in task performance during a pre-experimental baseline task, OAs performed equivalently to YAs when all cues were available, but worse than YAs as the number of cues decreased. These findings suggest spatial pattern completion may be impaired in OAs. We discuss these findings in the context of a growing body of literature suggesting age-related imbalances in pattern separation versus pattern completion.